Study on enzyme activities in pineapple fruit and pineapple waste to be applied as poultry supplement - N. A. M., Ridzuan; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; N., Masngut; N., Zainol; Jun Haslinda, Shariffuddin (IOP Publishing, 2020)
Pineapple fruit contains essential minerals and vitamins with some medicinal values. Hence, it can be used as a raw material to make poultry supplements. Abundance of pineapple waste also has led to the environmental problems such as producing bad odor and has increased waste capacity in the landfill. In this present work, the potential of pineapple fruit and pineapple waste were investigated to be used as the raw materials for poultry supplement based on their enzyme activities. In this study, the effect of fermentation time and type of pineapple substrates on enzyme activities which were xylanase, total cellulase and protease were studied. Two types of pineapple samples have been used in this study which were pineapple fruit and pineapple waste. Four type of pineapple substrates have been prepared which were pineapple juice, pineapple waste, pineapple juice + probiotic and pineapple waste + probiotic. The purpose of adding probiotic in this study was to enhance the fermentation reaction. The results showed that the fermentation time that have the highest enzyme activities for xylanase, total cellulase and protease were observed at day 2, 4 and 6 respectively, where substrate contains pineapple juice + probiotic recorded the highest enzyme activities value for all the three enzymes. This study had investigated that pineapple fruit and pineapple waste contain digestion enzymes which were xylanase, protease and cellulase that can be applied as poultry supplements.